Well-rounded lattices via polynomials with real roots - Alves, Carina [UNESP] (2020)
Well-rounded lattices have been a topic of recent studies with applications in wiretap channels and in cryptography. A lattice of full rank in Euclidean space is called well-rounded if its set of minimal vectors spans the whole space. In this paper, we investigate the well-roundedness of lattices coming from polynomials with integer coefficients and real roots.